Clinical and economic impact of multipoint left ventricular pacing: A comparative analysis from the Italian registry on multipoint pacing in cardiac resynchronization therapy (IRON‐MPP). (12th March 2020) - Forleo, Giovanni B.; Santini, Luca; Calò, Leonardo; Ricciardi, Danilo; Curnis, Antonio; Pignalberi, Carlo; Calzolari, Vittorio; Giammaria, Massimo; Morani, Giovanni; Bertaglia, Emanuele; Ribatti, Valentina; Biffi, Mauro; et al.
Abstract: Introduction: Early evidence suggests that multipoint left ventricular pacing (MPP) may improve response to cardiac resynchronization therapy (CRT). It is unknown whether this benefit is sustained and cost‐effective. We used real‐world data to evaluate long‐term impact of MPP‐ON clinical status, heart failure hospitalizations (HFH) and costs. Methods: The Italian registry on multipoint left ventricular pacing is a prospective, multicenter registry of patients implanted with MPP‐enabled CRT devices. For this analysis, clinical and echocardiographic data were collected through 24 months and compared between patients with (MPP‐ON) or without (MPP‐OFF) early MPP activation at implant. The total cost of each HFH was estimated with national Italian reimbursement rates. Results: The study included 190 MPP‐OFF and 128 MPP‐ON patients with similar baseline characteristics. At 1 and 2 years, the MPP‐ON group had lower rates of HFH vs MPP‐OFF (1‐year hazard ratio [HR]: 0.14, P = .0014; 2‐year HR: 0.38, P = .009). The finding persisted in a subgroup of patients with consistent MPP activation through follow‐up (1‐year HR: 0.19; P = .0061; 2‐year HR: 0.39, P = .022). Total HFH per‐patient costs were lower in the MPP‐ON vs the MPP‐OFF group at 1 year (€101 ± 50 vs €698 ± 195, P < .001) and 2 years (€366 ± 149 vs €801 ± 203, P = .038). More MPP‐ON patients had ≥5% improvement in ejection fraction (76.8% vs 65.4%, P = .025) and clinical composite score (66.7% vs 47.5%, P = .01). Conclusions: In this multicenter clinical study, early MPP activation was associated with a significant reduction in cumulative HFH and related costs after 1 and 2 years of follow‐up.